2012
DOI: 10.1542/peds.2011-3328
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Critically Ill Children

Abstract: We found a high rate of vitamin D deficiency in critically ill children. Given the roles of vitamin D in bone development and immunity, we recommend screening of those critically ill children with risk factors for vitamin D deficiency and implementation of effective repletion strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
134
3
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(171 citation statements)
references
References 43 publications
24
134
3
10
Order By: Relevance
“…In agreement with our results, Madden et al (20) , studied 511 critically ill children admitted to Boston Children's Hospital PICU. They found a high rate of vitamin D deficiency in their critically ill children as 40.1% of cases were vitamin D deficient.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our results, Madden et al (20) , studied 511 critically ill children admitted to Boston Children's Hospital PICU. They found a high rate of vitamin D deficiency in their critically ill children as 40.1% of cases were vitamin D deficient.…”
Section: Discussionsupporting
confidence: 92%
“…(15) Though high prevalence of vitamin D deficiency in critically ill adults and children has been documented, the impact of such deficiency is not yet clear. Few studies have documented significant association of deficiency with poor outcomes such as longer duration of ICU stay (16,17) , increased inotropic requirement (18,19) and higher admission illness severity scores (16,20) All the parents or the legal guardians of the patients enrolled in this study signed a written informed consent before participation. The study was approved by the Medical Ethics Committee of the Faculty of Medicine, Alexandria University.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies of vitamin D deficiency in the pediatric intensive care unit (ICU) (PICU) population have reported a prevalence of between 30 and 86% (18)(19)(20)(21). We found lower 25(OH)D levels to be associated with greater illness severity (22); other pediatric critical care studies have confirmed this finding (19,21,23,24), although equal numbers have reported no correlation with illness severity or ICU outcomes (18-20, 25, 26). Despite the rapidly increasing volume of evidence linking 25(OH)D deficiency with ICU morbidity and mortality over the past 10 years (1-4, 6-8, 10, 11, 27, 28), the question of whether vitamin D repletion will improve clinical outcomes in critical illness remains unclear.…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 40%
“…These are the same risk factors we identified for low total 25(OH)D in the same population of children. Because lower circulating VDBP levels increase the proportion of 25(OH)D that is bioavailable, it follows that the total (22). We believe these results are an important consideration when interpreting total 25(OH)D levels in critically ill children, especially those at higher risk for low VDBP levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation